2016
DOI: 10.1111/apt.13696
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of ledipasvir/sofosbuvir ± ribavirin vs. ombitasvir/paritaprevir/ritonavir + dasabuvir ± ribavirin in 6961 genotype 1 patients treated in routine medical practice

Abstract: In this robust real-world cohort, SVR rates were similar to clinical trials. FIB-4 > 3.25 and high BMI were significant negative predictors of SVR. Reduced odds of SVR in African Americans and with OPrD + RBV likely arose from excess early discontinuation as these factors were no longer significant, when limited to patients completing a 12-week course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
62
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 27 publications
13
62
2
Order By: Relevance
“…These rates were similar to the 92.9% or 92% SVR rates derived from the first regimen presented in two US VA National Healthcare System studies[18,19] and the 94.9% or 95.1% SVR rates achieved with the second regimen in other studies in clinical practice[18,20]. …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These rates were similar to the 92.9% or 92% SVR rates derived from the first regimen presented in two US VA National Healthcare System studies[18,19] and the 94.9% or 95.1% SVR rates achieved with the second regimen in other studies in clinical practice[18,20]. …”
Section: Discussionsupporting
confidence: 84%
“…Most real-world studies reported results in genotype 1 HCV patients[14,19,20]. The SVR rate in our study, which included 362 genotype 1 patients, was 94.5% of the overall genotype 1 patients, which was somewhat higher than previously reported rates (SVRs over 91%), although limited differences were observed among the different DAA combinations, treatment durations and use of RBV.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The therapeutic success increased significantly to 95%-97% Sustained Viral Response (SVR) depending on the fibrosis stage and cirrhosis [5][6][7][8][9]. Therefore a necessity of earlier diagnosis became indubitable to prevent the future complications and deaths.…”
Section: Introductionmentioning
confidence: 99%
“…While several observational studies [5, 6, 1316] have studied DAA treatment effectiveness among cohorts with cirrhosis and human immunodeficiency virus (HIV) or through the United States Veterans Administration [13, 17], no study has evaluated the effectiveness among a diverse group of participants from a general population as large as that available in Clalit Health Services (CHS).…”
Section: Introductionmentioning
confidence: 99%